Li-Ion solvation in propylene carbonate electrolytes determined by molecular rotational measurements. Issue 20 (8th May 2019) - Jiang, Haotian; Zhang, Qi; Zhang, Yutong; Sui, Laizhi; Wu, Guorong; Yuan, Kaijun; Yang, Xueming
Abstract : We report the solvation structure of Li + in LiPF6 –PC solutions using ultrafast vibrational spectroscopy. The results illustrate the salt concentration-dependent solvation structures, in accordance with the variation of ion conductivity. Abstract : Lithium-ion batteries are an attractive power source for a wide variety of applications. Expanding the performance limit of current Li-ion batteries requires ion–solvent interaction, which governs the ion transport behavior of electrolytes, to be fully understood. We herein examine the coordination number of the Li + ion in LiPF6 –PC solutions using femtosecond vibrational spectroscopy. Surprisingly, we found that the coordination number of PC in the first solvation shell of Li + decreases from 4 to 2 as the salt concentration increases. At dilute salt concentrations, the Li(PC)4 + complex with a tetrahedral geometry is dominant, while at high salt concentrations, the presence of anions in the first solvation shell modifies the solvation structure, leading only 2 PC molecules to coordinate to Li + directly. The variety of the solvation structure provides a rational explanation for the ionic conductivity changing as the salt concentration increases.